Mechanical properties of experimental resin cements containing different photoinitiators and co-initiators - Lima CR; Silva DB; Vitti RP; Miranda ME; Brandt WC (Dove Medical Press, 2019)
Carla dos Reis Lima,1 Danilo Bandeira da Silva,2 Rafael Pino Vitti,3 Milton Edson Miranda,1 William Cunha Brandt21Department of Prosthodontics, São Leopoldo Mandic, Campinas 13045-541, SP, Brazil; 2Department of Implantology, University of Santo Amaro, São Paulo 04743-030, SP, Brazil; 3Department of Dentistry, Herminio Ometto University Center, Araras 13607-339, SP, BrazilCorrespondence: Rafael Pino VittiDepartment of Dentistry, Herminio Ometto University Center, Av. Dr. Maximiliano Baruto, 500, Araras 13607-339, SP, BrazilTel/Fax +55 193 543 1400Email rafapvitti@gmail.comAim: The aim of this study was to evaluate the influence of different concentrations of two photoinitiators and one co-initiator on the flexural strength (FS) and elastic modulus (E) of experimental resin cements.Materials and methods: A mixture containing BisGMA, TEGDMA, and barium-aluminum-silicate (BaAlSi) and silanized colloidal silica (SiO2) filler particles was prepared with two photoinitiators, viz. camphorquinone (CQ) and bisacylphosphine oxide (BAPO). Dimethylaminoethyl methacrylate (DMAEMA) was used as co-initiator. Thirty groups (n=10) were formulated with different photoinitiator systems (CQ/DMAEMA and BAPO/DMAEMA) and concentrations (wt%) of photoinitiator and co-initiator. The photoactivation was carried out for 20 s with a light-emitting diode (LED, Bluephase, Ivoclar Vivadent) with irradiance of 1200 mW/cm2. The FS and E were obtained in a three-point bending test on a universal testing machine (0.5 mm/min). Data were subjected to the Kolmogorov-Smirnov normality test, followed by two-way ANOVA and Tukey’s test (α=0.05).Results: No polymerization occurred in the CQ groups without DMAEMA (0 wt%). DMAEMA 0.5 %wt and 1 %wt groups showed statistically similar FS and E results for CQ and BAPO, except for CQ 0.3 wt% (FS), CQ 0.9wt% (E) and BAPO 1.76 wt% (FS and E) for DMAEMA 0.5 %wt. No significant difference was found for FS and E values for different concentrations of photoinitiators, except for CQ 0.25 wt% (FS and E) and BAPO 0.25 wt% (E) that showed the lowest values.Conclusion: The wt% of the photoinitiators and co-initiator influenced the mechanical properties and the performance of CQ was dependent on the DMAEMA concentration. BAPO can be used as substitute for the conventional CQ/DMAEMA photoinitiator system.Keywords: mechanical properties, monomers, photoinitiators, resin cements